2018
DOI: 10.1111/ajt.14531
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach to cardiac and pulmonary vascular disease risk assessment in liver transplantation: An evaluation of the evidence and consensus recommendations

Abstract: Liver transplant (LT) candidates today are older, have greater medical severity of illness, and have more cardiovascular comorbidities than ever before. In addition, there are specific cardiovascular responses in cirrhosis that can be detrimental to the LT candidate. Cirrhotic cardiomyopathy, a condition characterized by increased cardiac output and a reduced ventricular response to stress, is present in up to 30% of patients with cirrhosis, thus challenging perioperative management. Current noninvasive tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
181
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(190 citation statements)
references
References 138 publications
4
181
0
2
Order By: Relevance
“…(18) In addition, some studies have already shown the association of those factors with CAD in patients with end-stage liver disease. (4,18) Finally, a recent multidisciplinary consensus recommendation suggests coronary angiography in all candidates with diabetes alone or at least 2 other CVR factors, (22) thus reinforcing the appropriateness of our selected high-risk population. Unfortunately, we were unable to detect a clinical risk profile predictive of severe coronary disease.…”
Section: Discussionmentioning
confidence: 91%
“…(18) In addition, some studies have already shown the association of those factors with CAD in patients with end-stage liver disease. (4,18) Finally, a recent multidisciplinary consensus recommendation suggests coronary angiography in all candidates with diabetes alone or at least 2 other CVR factors, (22) thus reinforcing the appropriateness of our selected high-risk population. Unfortunately, we were unable to detect a clinical risk profile predictive of severe coronary disease.…”
Section: Discussionmentioning
confidence: 91%
“…LT candidates with traditional absolute cardiac contraindications to proceeding with transplant were not included in this analysis. Traditional absolute cardiac contraindications at most transplant centers include: (1) decreased left ventricular systolic function (ejection fraction <45%), (2) decreased right ventricular function and/or significant right ventricular dilation, (3) uncontrolled pulmonary hypertension defined as mean pulmonary artery pressure ≥35 mm Hg at rest despite maximal medical management, (4) significant uncorrectable structural valvular abnormalities (aortic stenosis, mitral stenosis, aortic regurgitation, tricuspid regurgitation), (5) uncorrectable coronary artery disease with induced ischemia on stress testing, (6) significant carotid disease in particular if symptomatic, and (7) diffuse atherosclerotic disease involving multiple organs …”
Section: Estimated Prevalence Of Cardiovascular Risk Factors Among LImentioning
confidence: 99%
“…(6) Even without our requested findings, we would make the statement that all HR-NASH liver transplant candidates should undergo pretransplantation coronary angiography given the high pretest probability for obstructive CAD and the inferior posttransplant outcomes. In further support of this statement, a recent multidisciplinary consensus recommendation by VanWagner et al (10) suggests performing coronary angiography in all candidates with diabetes alone or 2 traditional cardiovascular risk factors (Grade 2C evidence). Further multicenter, largescale prospective studies to better validate these recommendations seems warranted at this time.Ultimately, our goal as liver transplant providers and researchers is to maximize organ utility given the inequity between supply and demand.…”
mentioning
confidence: 99%